Proposal for a water resource management strategy model using the water footprint concept - Costa, Leonardo; Amato Neto, João (Brazilian Journal of Operations & Production Management, 2017)
We hereby present a proposal for a water stewardship strategy model, having the water footprint as a reference, developed from the results of a qualitative and exploratory research and by interviews with experts in the subject. The aim is to identify these experts’ contributions to a water stewardship model as from the applicability of the water footprint concept. From the contribution provided by the experts’ panel, as well as the authors’ understanding of the content of the bibliographic research conducted, a water stewardship strategy model was proposed for producing goods and services as from the water footprint concept, structured as a Plan-Do-Check-Action stewardship model. This model sought to be supported on a holistic view of the sustainable management process of water resources, besides seeking to provide an innovative and comprehensive way to account for water use and consumption along with effluent disposal. Thus, it sought to contribute to a suitable risk management and might contribute as a necessary support for the development of operational and commercial strategies, contributing significantly to the sustainable development of an organization.